Analysis of pollutant emissions and fuel consumption, during real driving cycles in different intake temperature scenarios. (February 2023) - Luján, Jose M; Climent, Hector; Ruiz, Santiago; Redondo, Fernando
Current European vehicle homologation regulations are increasingly restrictive. Recently, World-wide light-duty test cycle (WLTC) and Real driving emissions (RDE) cycles have been introduced as type approval tests for new vehicles. This document studies the effect of intake temperature on pollutant emissions and fuel consumption of a Euro 6 Diesel engine when tested under WLTC and RDE. The tests have been performed by setting the temperature at the outlet of the water charge air cooler (WCAC) at 35°C and 20°C in different tests. To do that, the air-cooler was immersed in a temperature-controlled water bath. This temperature reduction can be produced due to an improvement in the WCAC in the same ambient temperature or also with the same WCAC in case of the ambient temperature is lower. All tests have been carried out in an engine test bench, eliminating the uncertainty involved on the road (driving mode, traffic, ambient temperature, etc.). Once the WLTC and RDE cycles were performed, carbon dioxide (CO2 ) and pollutant results were analyzed. Nitrogen oxides (NOX ) emissions were considerably reduced when the engine intake temperature air was decreased, concretely a 7.1% in RDE and 11.63% in WLTC and the CO2 emissions were also cut down around 1%.